Correlation of serum opsonins with in vitro phagocytosis of Streptococcus pneumoniae. - Chudwin, D S (1985)
C-reactive protein (CRP), an acute-phase reactant which binds to phosphocholine (PC) in the pneumococcal cell wall, and anti-PC antibodies are protective against experimental pneumococcal bacteremia in mice. To determine the relative opsonic capacities of CRP and anti-PC compared with those of antibodies against pneumococcal capsular polysaccharides (anti-PCP), we correlated in vitro opsonic activity for serotype 7F Streptococcus pneumoniae with concentrations of CRP, anti-PC, and anti-type 7F PCP in human sera from 10 normal subjects and 38 patients with sickle cell (SS) disease, a high-risk group for pneumococcal infection. Opsonic activity, measured by a radiolabeled bacterial uptake assay, correlated with anti-PCP levels but not with CRP or anti-PC in both the normal subjects and patients with SS disease. Addition of CRP to normal sera did not increase opsonic activity for serotypes 4 and 7F S. pneumoniae, although it did so for serotype 27, a nonpathogenic strain unique for having PC in its capsule. CRP and anti-PC were not effective opsonins when they bound to the pneumococcal cell wall rather than the capsule. The protective effects of CRP or anti-PC against these serotypes may be produced by means other than complement-dependent opsonization.